2020
DOI: 10.1515/biol-2020-0089
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30c-5p/ROCK2 axis regulates cell proliferation, apoptosis and EMT via the PI3K/AKT signaling pathway in HG-induced HK-2 cells

Abstract: Diabetic nephropathy (DN) is one of the most common complications of diabetes mellitus. Increasing evidence suggests that microRNA-30c-5p (miR-30c-5p) participates in the pathogenesis of DN, but the mechanism has not been clearly understood. Therefore, this study aimed to investigate the biological role of miR-30c-5p in human DN progression in vitro. Compared with the controls, DN tissues and high glucose-induced HK-2 cells had significantly reduced miR-30c-5p levels, while ROCK2 expression was prominently ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Another target of miR-30c is the regulatory subunit of phosphoinositide-3-kinase (PI3K), which phosphorylates phosphatidylinositol 4,5-bisphosphate to generate phosphatidylinositol 3,4,5-trisphosphate (PIP3) which, in turn, allows the recruitment of AKT1 to the membrane [ 36 ]. This enzyme plays a key role in glucose tolerance improvement by facilitating the effect of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Another target of miR-30c is the regulatory subunit of phosphoinositide-3-kinase (PI3K), which phosphorylates phosphatidylinositol 4,5-bisphosphate to generate phosphatidylinositol 3,4,5-trisphosphate (PIP3) which, in turn, allows the recruitment of AKT1 to the membrane [ 36 ]. This enzyme plays a key role in glucose tolerance improvement by facilitating the effect of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…For in vitro transfection, 100 nM miR-30c-5p mimic (sequence: 5'-UGUAAACAUCCUACACUCUCAGC-3'), miR-30c-5p inhibitor (sequence: 5'-GCUGAGAGUGUAGGAUGUUUACU-3'), miR-30c-5p mimics control (sequence: 5'-CUAACGCAUGCACAGUCGUACG-3') ( 35 ), miR-30c-5p inhibitor control (sequence: 5'-CAGUACUUUUGUGUAGUACAA-3') and, which were from Nanjing Synthgene Medical Technology Co., Ltd, were transfected into RPM cells using Lipofectamine 2000 (Invitrogen; Thermo Fisher Scientific, Inc.) for 48 h at 37˚C according to the manufacturer's instructions. miR-30c mimic was co-transfected with 5 µg plasmid pcDNA3.1-SOX9-Flag (Nanjing Synthgene Medical Technology, Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…Existing evidence suggests that miR-30c attenuates cardiovascular dysfunctions [51][52][53], hyperglycemia [54][55][56], obesity [57], atherosclerosis [58][59][60], dyslipidemia [17], and hepatic lipoprotein production [61,62], which constitute major risk factors in stroke and other neurological disorders. MiR-30c potentiates prosurvival anti-apoptotic pathways [63][64][65]. Experimental findings indicated that in the initial stages of ischemia suppression of autophagy by miR-30c may worsen neurodegeneration in the spinal cord I/R injury model [66].…”
Section: Role Of Mir-30c In Neurological Disordersmentioning
confidence: 99%